Labial salivary gland biopsy: a crucial method for confirming seronegative Sjogren’s syndrome—a case report - Satyasai S. G. Romala; Kishore Moturi; Ravikanth Manyam; Meghana Vadupu; P. Divya Naga Lakshmi; Anil Budumuru; U. Shivajiraju; J. S. D. N. Sai Hyma; R. V. S. N. S. Ramachandrudu (Bulletin of the National Research Centre)
Abstract Background Sjogren’s syndrome is an autoimmune disease that affects exocrine glands like sweat glands, salivary glands, and lacrimal glands. Dentists frequently encounter these patients and have an important role in establishing the diagnosis. It is mainly diagnosed by clinical features like xerostomia and xerophthalmia, along with anti-Sjögren’s syndrome-related antigen A (anti-SSA/also called Ro antigen) and anti-Sjögren’s syndrome-related antigen B (anti-SSB/ also called La antigen) antibodies in the patients. However, there is a subset of the population where autonuclear antibodies cannot be detected but are still present with all clinical features of Sjogren’s syndrome. Such patients usually remain undiagnosed, and only symptomatic treatment is given in spite of repeated consultation with various medical specialists. Only after establishing a proper diagnosis can we initiate definitive treatment. Case presentation Here, we report a case of seronegative Sjogren’s syndrome in a patient with severe xerostomia without anti-SSA and anti-SSB antibodies. The focus score from the labial biopsy, co-relating with clinical presentation, helped us in establishing the diagnosis. After a definitive diagnosis, our patient is put on cholinergic therapy, which greatly reduced the symptoms of xerostomia. Conclusions Physicians and dentists should refer such patients to an oral and maxillofacial surgeon for a labial biopsy to consider “seronegative Sjogren’s syndrome." The “focus score” evaluation by the pathologist helps in establishing the diagnosis of “seronegative Sjogren’s syndrome”.